Credit of Apartment Ownership and Legal Protection for Debtors Against Construction Failure Risk - Muhammad Zaki Mubarrak (Greenation Research & Yayasan Global Resarch National, 2026)
One problem that requires attention is imbalance between debtor's financial obligations and buildings physical certainty (house/apartment), especially in indent scheme, which involve buying before physical house is completed. This KPRS scheme places of debtor in a vulnerable position, especially in a failed apartment construction project event. This problem is caused by the obligation to repay loan that has been ongoing since the agreement was signed, while the financed residential object has not been realized or functionally utilized. This study analyze the legal regulations for KPRS in national legal system and examine legal protection for debtors in failed apartment construction cases, by highlighting regulations fragmentation between banking law, housing law, and consumer protection law. This study uses a normative legal research method with a statutory and conceptual approach. Primary legal materials include laws and regulations in banking fields, apartment, consumer protection, and financial services sector regulation, while secondary legal material consist of legal literature and relevant court decisions. The analysis is conducted qualitatively through legal interpretation and systematic analysis to assess interrelationships between norms in apartment financing. The research finding indicate that KPRS regulation remain sectoral and not normatively integrated, resulting in suboptimal debtor protection. Housing law normalizes pre-construction marketing practices without guaranteeing substantial protection for debtor, while banking law emphasizes prudential principles oriented toward bank interests. Furthermore, consumer protection regime and financial service regulation have not specifically addressed apartment construction failure risk. This fragmentation results in KPRS debtors bearing a disproportionate risk of construction failure.